Growth mechanism, field emission and photoluminescence property of Ge-doped hexagonal cone-shaped GaN nanorods. (October 2018) - Li, Enling; Zhao, Binyue; Lv, Shitao; Cui, Zhen; Ma, Deming; Li, Meiqin
Abstract: The Ge-doped hexagonal cone-shaped GaN nanorods have been synthesized by the VLS process. The variation of N-rich condition and Ga-rich condition in reaction chamber results in the morphology of the Ge-doped GaN nanorods being hexagonal cone-shaped. The Ge-doped hexagonal cone-shaped GaN nanorods exhibit an excellent emission property with typical turn-on electric field as low as 2.93 V/μm, this indicates that the Ge-doped hexagonal cone-shaped GaN nanorods could be well used in cold cathode electron source applications. The photoluminescence spectrum of the Ge-doped hexagonal cone-shaped GaN nanorods indicates it could be applied in blue-violet and ultraviolet photoelectric devices. Highlights: Ge-doped hexagonal cone-shaped GaN nanorods have been prepared. Ge-doped hexagonal cone-shaped GaN nanorods possess have a lower turn-on field. Ge-doped hexagonal cone-shaped GaN nanorods have strength light emission peaks in blue-violet and ultraviolet. The variation of N-rich condition and Ga-rich condition in reaction chamber results in the morphology of the Ge-doped hexagonal cone-shaped GaN nanorod.